Pola Kepemimpinan Islam dalam Perbankan Syariah (Studi Kasus di Bank X Syariah Cabang Z) - Mardatillah Mardatillah (FEB Universitas Sultan Ageng Tirtayasa, 2020)
A succesful of a leader in order to reach the goals cannot be dismissed from the interaction between the leader and the inferior. In Islam, leadership is always related to responsibility, which bases on authority (shalahiyah) and the rights of taking decision assigned to a leader, the ideal side which always been hoped, but the other side is that there are still may of shari‟a banking which have not applied the leadership concept as it is hoped. Decription qualitative research is used by the writer to explain the case of this leadership which has been done by Bank X Syariah. The result of this research is that the leadership patter is participatif democratie. The way of its leader to settle the situation and condition which can courage the inferions ti be motivated to give them opinition or suggestion and also to give opportunity to show their succesful performance at work.